AI-Powered Transcreation in Global Marketing: Insights from Iran - Ghodrat Hassani; Marziyeh Malekshahi; Hossein Davari (ELOPE, 2025)
This study examines AI-powered transcreation’s role in improving cross-cultural brand communication. We employed GPT-3 to evaluate AI’s ability to enhance global marketing through improved translation and adaptation of brand messages. Traditional translation methods often fail to capture brand-specific emotional resonance across cultures, but AI tools may address this challenge. Our research compared 10 translation students and 10 professional translators in translating/transcreating brand taglines from Persian to English. An initial test without AI showed professionals outperforming students. After six weeks of GPT-3 training, however, students surpassed professionals, as judged by expert raters using standardized criteria. The findings indicate that targeted AI training can improve transcreation quality. The study also underscores the value of human judgment in crafting prompts and choosing optimal AI outputs. These results also offer insights for translation education, professional training, and global marketing strategies.